Theory, analysis & meaning in music - Pople, Anthony (Cambridge Cambridge University Press, 1994)
Recent encounters with structuralist and poststructuralist critical theory, linguistics, and cognitive sciences have brought the theory and analysis of music into the orbit of important developments in present-day intellectual history. Without seeking to impose an explicit redefinition of either theory or analysis, this book explores the limits of both. Essays on decidability, ambiguity, metaphor, music as text, and music analysis as cognitive theory are complemented by studies of works by Debussy, Schoenberg, Birtwistle and Boulez.